ANALYSIS OF OVERPRESSURE CHARACTERISTICS IN ESLE FIELD, SOUTH SUMATRA BASIN - Sebiatako Vera Sedayu, Enggels
This research was conducted in a field in the South Sumatra Basin, namely the Esle Field. The South Sumatra Basin is known to have an overpressured zone. Pore pressure analysis is needed to avoid drilling risks due to overpressure, such as blowout, kick, and loss. In addition, overpressure analysis is also needed to prevent technical and financial losses from further drilling. The purpose of this study is to estimate pore pressure using wire line log data, determine the depth of top of overpressure, determine the overpressure generating mechanism, and analyze the relationship between geological conditions and the presence of overpressure in the study area. Data processing was carried out on three wells (Esle-1, Esle-2, and Esle-3) in the Esle Field using Microsoft Excel. The data processed were wire line log data, drilling reports, temperature data, seismic data, and mud weight data. The top of overpressure in the Esle-1 and Esle-2 is at a depth of 2500 meters. While in the Esle-3, the top of overpressure is at a depth of 3000 meters. This overpressure zone is found in the Gumai Formation at the claystone interval. The pore pressure in the overpressure zone ranges from 4200 – 10000 psi. Overpressure with loading mechanism ranges from a depth of 2455.1 m-2900 m. While the non-loading overpressure ranges from a depth of 2900 m-3500 m. The results show that the pore pressure is in overpressure condition due to loading and nonloading mechanisms. Overpressure with non-loading mechanism in the study area is influenced by clay mineral diagenesis and hydrocarbon maturity. Meanwhile, the overpressure generated by the loading mechanism is caused by the disequilibrium compaction.